Does Context Matter? Examining the Effectiveness of Contextual Approach on Mathematical Problem-Solving in Function Composition - Nasrullah Pemu (International journal of technology and education research, 2026)
Mathematical problem-solving ability is a crucial competency in mathematics education. This study aims to examine the effectiveness of the contextual approach on the mathematical problem-solving ability of Grade XI students at SMA Negeri 17 Makassar. The study employed a pre-experimental design with a One Group Pretest-Posttest model. The sample consisted of 26 students in class XI.2 selected through cluster random sampling. Data were collected through problem-solving tests (pretest and posttest), classroom observation sheets for learning implementation and student activity, and a student response questionnaire. Data were analyzed using descriptive statistics and nonparametric inferential statistics (Wilcoxon Signed Rank Test, One Sample Wilcoxon Signed Rank Test, and Binomial Test). Results showed that: (1) the learning implementation reached 93.75% (very good category); (2) student activity reached 93.75% (very active category); (3) the mean posttest score was 85.05 with a classical completeness rate of 96.15%, exceeding the 80% standard; (4) the normalized gain mean was 0.84 (high category); and (5) student responses reached 76.44% (tending positive category). Inferential test results confirmed that the contextual approach significantly improved students' mathematical problem-solving ability (p < 0.05). This study concludes that the contextual approach is effective in improving students' mathematical problem-solving ability on the topic of function composition.